Holistic Islamic Model for Securing Wealth in Light of Maqasid-E-Shariah - Dr. Muhammad Akram Hureri; Muhammad Omer Rafique; Dr. Khushbakhat Alia; Dr. Muhammad Zia Ullah; Dr. Muhmood Ahmad; Dr. Abdul Majid (Al-Qanṭara, 2022)
Abstract: Wealth is one of the dearest things to human. He is always concerned about its security, but the problem is that the modern systems have failed to protect the wealth and provide satisfaction to the owner. One of the examples is increasing of cyber thefts. The study aims to find out the model of Islam provided for securing wealth, because it claims to solve every problem of human life. The research has adopted the qualitative design to fulfill the objective. The research analyses the textual data from authentic sources of Islamic content and adopts grounded theory approach to form a model with the linkages of varied text used in content about securing wealth. The study concludes with a model based on five pillars, namely: Circulation of wealth, Equitable distribution, Clear transactions, No lavishness and Chastisements on violation. The implementation of this model with all its requisites ensures the security of individual’s wealth as well as the wealth of a nation as a whole. The significance of the study is visible, because being a Muslim it is our responsibility to introduce the Islamic solutions to our social and legal problems.